Shape memory polymers as actuators: Characterization of the relevant parameters under constrained recovery. Issue 10 (18th August 2021) - Peixoto, Carina; Zille, Andrea; Ferreira da Silva, Alexandre; Carneiro, Olga Sousa
Abstract: In this work, a shape memory polyurethane is characterized through constrained recovery experiments performed in a tensile testing equipment. The most relevant results obtained are those concerned with the stress released over time during the recovery stage, since they provide quantitative information that can be used in the design of actuators. For this sake, design guidelines are proposed based on the effect of: (i) the programming temperature; (ii) the deformation imposed during the programming stage; (iii) the recovery temperature; and (iv) the manufacturing process used to produce the samples tested (compression molding and Fused Filament Fabrication). The set of experiments performed with compression‐molded samples put in evidence a considerable variety of material responses: (i) the maximum released stress varied from 0.74 to 1.68 MPa; (ii) the time required to attain this stress varied from 47 to 600 s; and (iii) the stress was released as a peak value that relaxed rapidly, or, contrarily, had a lasting effect. Another relevant conclusion is that the 3D printing technique does not affect the shape memory behavior of the material. Having this in mind, the conclusions provided by the compression‐molded samples study can be extended to printed ones. Abstract :